HUBUNGAN ANTARA FAKTOR-FAKTOR DIMENSI STAFFING DENGAN BUDAYA KESELAMATAN PASIEN DI RUMAH SAKIT TNI-AU DR. ABDUL MALIK LANUD SOEWONDO MEDAN TAHUN 2020 - Lubis, Afrillah Chairani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Safety culture is key to supporting the improvement of occupational safety and health within the organization. One dimension that is considered important can affect the incidence of patient safety incidents in RSAU dr. Abdul Malik Medan is the dimension of staffing. The staffing dimension in question is the process of structuring staff in the unit to handle workload, working hours, work team, work stress, which is appropriate to provide good service for patients. This research is quantitative analytic with a sectional case research design with a sample count of 42 people. The data was analyzed with chi-square bivariate test with α 0.05 and Multivariate Test (Multiple Logistics Regression). The results of the chi-square bivariate analysis showed that there was a significant relationship between working hours and patient safety culture judging by the p (Sig) value of 0.012 < 0.05 and pr score of 2.3 (95% CI : 1,717 – 28,545). There is a significant relationship between workload and patient safety culture judging by the p (Sig) value of 0.033 < 0.05 and the PRvalue of 1.88 (95% CI : 1,348 – 21,639). There is a significant relationship between the work team and the patient safety culture judging by the p (Sig) value of 0.04< 0.05 and the PR value of 1.88 (95% CI : 2,193 – 38,933). There is a significant relationship between work stress and patient safety culture judging by the p (Sig) value of 0.019 < 0.05 and PR score 2 (95% CI : 1,522 – 23,427). As for the results of multivariate analysis (multiple logistic regression) for all variables shows a relationship between working hours, workload, work team and work stress to patient safety culture. The results of the analysis found the Odds Ratio (OR) of work stress variables was 14,879 meaning the stress felt by health workers.